Nutritional status of children from three to five years old in three districts of Lima. Peru, 2016 - Navarrete Mejía, Pedro Javier (2016)
Objective: To know the nutritional status of children from 3 to 5 years old living in the districts of Villa el Salvador, San Juan de Miraflores and San Juan de Lurigancho for the period from April to June 2016. Material and methods: Prospective, transversal, non-experimental study. The information includes 1,416 children from the districts of Villa El Salvador, Villa Maria del Triunfo and San Juan de Lurigancho (340, 322 and 754 respectively). The information collected included data on weight, height and age and based on this information, chronic malnutrition, acute malnutrition, overweight and obesity was determined according to the reference standard of the World Health Organization. S/Aand W/S indicators was calculated. Results: It was determined that the population of San Juan de Lurigancho had higher chronic malnutrition (8.6 %) and higher overweight (11.0 %) , the population of the district of Villa Maria del Triunfo had higher acute malnutrition (1.3 %) and population of Villa El Salvador greater obesity (4.6 %). Conclusion: In recent years the nutritional issue has a major boost by the Peruvian government through social programs, focusing on the determinants level of causality. Today only food security, maternal and child care and environmental quality are observed, neglecting health approach causality, considered the most important approach to the problem. Large national guidelines on nutrition strategies should include not only reduction of nutritional problems but also preventing these.